Ergot in Canadian cereals – relevance, occurrence, and current status. Issue 6 (2nd November 2022) - Walkowiak, Sean; Taylor, Dale; Fu, Bin Xiao; Drul, Dainna; Pleskach, Kerri; Tittlemier, Sheryl A.
Abstract: Ergot is a fungal disease that occurs on cereals and grasses, including rye, oat, wheat, and barley. The ergot pathogen, Claviceps purpurea, infects the floret, and as infection progresses, it replaces individual kernels, appearing on the head as darkly coloured fungal bodies called sclerotia. Ergot is a grain-grading factor in Canada and can affect grain quality and value, as well as safety due to production of ergot alkaloids. Testing of durum fortified with ergot sclerotia showed that the presence of sclerotia resulted in black specks in semolina and pasta, but had no impact on milling performance or end-product quality. Surveillance performed as part of the Canadian Grain Commission's annual Harvest Sample and Cargo Monitoring Programs provided insights into ergot incidence and severity in different grains, growing locations, and years, as well as the presence of ergot alkaloids. Analysis of more than 230 000 Harvest Sample Program grain samples from western Canada across 25 years showed the highest ergot incidence and severity occurred in rye, followed by bread and durum wheat, and then barley and oats. Ergot incidence and severity varied annually, but only incidence increased over time. Analyses of bulk grain shipments indicated that the presence of ergot alkaloids reflected the disease incidence observed in the harvest samples (median ergot alkaloid concentrations in wheat and durum > oats and barley). Data on ergot alkaloids from the Cargo Monitoring Program also showed that the Canadian bulk grain-handling system mitigated the variability in annual ergot incidence and severity observed in harvest samples.